2013
DOI: 10.1007/s00455-013-9484-7
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia Associated with Cervical Spine and Postural Disorders

Abstract: Difficulties with swallowing may be both persistent and life threatening for the majority of those who experience it irrespective of age, gender, and race. The purpose of this review is to define oropharyngeal dysphagia and describe its relationship to cervical spine disorders and postural disturbances due to either congenital or acquired disorders. The etiology and diagnosis of dysphagia are analyzed, focusing on cervical spine pathology associated with dysphagia as severe cervical spine disorders and postura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 55 publications
0
60
0
Order By: Relevance
“…It is well-known that the DCFs are weakened in cervical kyphosis [1718]. Although the DCFs do not play a major role in swallowing function, a review article on dysphagia related to cervical and postural disorders suggested that weakening of the DCFs (longus colli and longus capitis) could cause problems in the swallowing process [1]. In particular, the longus colli muscle stabilizes the cervical spine during talking, coughing, and swallowing, and weakening of this muscle reduces stability during swallowing [19].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is well-known that the DCFs are weakened in cervical kyphosis [1718]. Although the DCFs do not play a major role in swallowing function, a review article on dysphagia related to cervical and postural disorders suggested that weakening of the DCFs (longus colli and longus capitis) could cause problems in the swallowing process [1]. In particular, the longus colli muscle stabilizes the cervical spine during talking, coughing, and swallowing, and weakening of this muscle reduces stability during swallowing [19].…”
Section: Discussionmentioning
confidence: 99%
“…The normal angle of curvature varies according to sex, age, and measuring methods of reporters. Various methods are currently used to measure the curvature of the cervical spine, including McGregor's line and the Harrison posterior tangent method; however, measurement of Cobb's angle is the most commonly used method, which defines angles between 20° and 60° as normal cervical curvature [1]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both configurations demonstrate the importance of head and neck posture as a functional module, which is underscored by dysphagia associated with cervical neck disorders. 42…”
Section: The Four Functional Modules Of Swallowing Mechanics (Hypothementioning
confidence: 99%